Optimization and Energy Maximizing Control Systems for Wave Energy Converters - Giorgi, Giuseppe; Sirigu, Sergej Antonello (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book, "Optimization and Energy Maximizing Control Systems for Wave Energy Converters", presents eleven contributions on the latest scientific advancements of 2020-2021 in wave energy technology optimization and control, including holistic techno-economic optimization, inclusion of nonlinear effects, and real-time implementations of estimation and control algorithms.